Inventory Control Analysis with Continous Review System and Periodic Review System Methods at PT. XYZ - Kurniawan, Shelvy; Saragih, Melva Hermayanty; Angelina, Vivi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2022)
Companies must have various strategies in order to survive and face the competition in the retail industry, where the strategy can be in the form of inventory control. The objective of this research is to categorize products owned by PT. XYZ based on the ABC analysis method, to analyze the best forecasting method for PT. XYZ for Filo Compound, Meses Valentino and Mercolade Dark 1 KG, to analyze the total cost using Q-Method & P-Method, and last to compare among Q-Method, P-Method and PT. XYZ’s policy. By doing ABC analysis, company is able to know which products to be prioritized. Forecasting is the first step to find out how much demand is expected in the future by analyzing demand data from the previous period. By having the smallest error which is reflected by MAD and MSE value, Trend Projection is the best method for forecasting as compared to the other five methods. Furthermore, this research is calculating the total cost by using the Q method and P Method to find out the best method with the smallest total cost for PT. XYZ. Q method is the best for Filo Compound and Meses Valentino with the cost saving as much as Rp 38.582.771,08 and Rp 43.215.539,68. While for the Mercolade Dark 1 KG, P Method is the best method with the cost saving as much as Rp 200.290.337,56.